Anaerobes Isolated From Clinical Material Over Three Years - Gubina, Marija; Urbančič-Rovan, Vilma; Tomič, Viktorija (Anaerobe, 1997)
Data on anaerobic bacteria isolated from clinical specimens at the bacteriology department within the 3-year period (1992–1994) were analysed. Anaerobic cultivation was carried out in all aspirates and swabs were transferred in transport media in syringes or blood cultures. Established growth occurred in all samples cultivated in thioglycollate broth after 4 days of incubation. Cultivation methods included enrichment media, GasPak jar, and API (BioMerieux) for final identification. A sulfite-reduction test using the Wilson–Blair medium and the Ellner–Smith sporulation medium was also used for the isolation ofClostridium perfringens. Anaerobes were diagnosed in 899 samples. Wound swabs (266 samples) and aspirates (106 samples) were the most common clinical material used. In total, 964 anaerobes were isolated:Peptostreptococcusspecies (299 strains),Eubacteriumspecies (188 strains),Propionibacteriumspecies (153 strains),Bacteroides fragilis(149 strains),Bacteroidesspecies (95 strains) andClostridium perfringens(80 strains).